Analisis Etika Komunikasi Pendakwah di Media Sosial Perspektif al-Qur’an - Khoirinnisa; Nasrulloh (Al-Kindi, 2026)
The development of technology in the digital era has changed the pattern of interaction and communication of the community, including in the practice of da'wah. Generation Z as active users of social media makes digital platforms as one of the spaces to obtain religious information. Conditions like this require preachers to not only understand the substance of Islamic teachings, but also to master communication ethics in accordance with the guidance of the Qur'an and Hadith. This study aims to analyze the communication ethics of preachers on social media by focusing on six principles of communication in the Qur'an, namely, qaulan sididan, qaulan baligha, qaulan ma'rufan, qaulan karima, qaulan layyina, and qaulan masyira. The research method uses a literature review approach through search of buu, scientific articles, and related journals. The results of this study show that the effectiveness of da'wah through digital is greatly influenced by the ability of preachers to convey messages honestly, politely, on target, and in accordance with the characteristics of the audience. In this study, it was also found that there is a tendency for some preachers to use harsh, degrading, or provocative language that has the potential to cause conflict and distance the next generation from Islamic values. Thus, the application of communication ethics is an important factor in ensuring that da'wah on social media still carries the value of rahmatan lil 'alamin and can be accepted constructively by generation Z.